2014
DOI: 10.1186/s13000-014-0191-y
|View full text |Cite
|
Sign up to set email alerts
|

InterTan nail versus Gamma3 nail for intramedullary nailing of unstable trochanteric fractures

Abstract: BackgroundTrochanteric fractures (TF) have become a major source of morbidity and mortality in elderly. We conducted this study to compare the outcomes of unstable trochanteric fractures treated with the InterTan nail and Gamma3 nail.MethodsBetween January 2008 and May 2013, patients aged 60 years or older with a diagnosis of unstable TF treated with InterTan nail or Gamma3 nail were included. Patients treated with InterTan nail were pair-matched to patients treated with Gamma3 nail in a 1:2 ratio. Radiographs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 26 publications
1
52
0
Order By: Relevance
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The mean duration of surgery for InterTan intramedullary nail in the late group of patients was 64.97 (95% CI 59.59 to 70.36) min, similar to the operative time reported in earlier research that ranged from 48 to 73.91 min [4, 5, 15, 1820], excluding one study that reported an average time that was less than 30 minutes [21]. These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes.…”
Section: Discussionsupporting
confidence: 83%
“…These studies also reported that the mean operative time for GN, PFNA, or PFNA-II treatments [4, 5, 15, 1820] was 44.41–72.98 minutes. Of these, two studies reported that there was no significant difference in the operative time between the InterTan intramedullary nail (IT) group and the GN or PFNA group [15, 20].…”
Section: Discussionmentioning
confidence: 91%
“…A previous clinical study reported that IT showed good clinical outcome and low complication rate in Asian patients 26 . However, when compared with 1-screw nailing system, patients treated with the IN nail showed similar HHS and experienced longer fluoroscopy and operative time 19 . It was not clear whether IT can provide better clinical outcomes.…”
Section: Discussionmentioning
confidence: 93%
“…For extremely unstable fracture situations, cerclage wiring or auxiliary plates have shown to improve biomechanical stability [26]. It appears that these biomechanical findings translate well into clinical practice [26,27].…”
Section: Treatment Of Trochanteric Fracturesmentioning
confidence: 94%